Computational Assessment of Biocompatibility and Toxicity of Graphene and Its Derivatives for Dental Adhesives - Ravinder Saini (Oral)
Background/Objectives: Graphene and its derivatives have garnered attention for their unique properties that could enhance dental biomaterials. Understanding their interactions with biological systems is crucial for optimizing their application in dentistry. This study aimed to comprehensively evaluate the biocompatibility, molecular interactions, and toxicity profiles of graphene and its derivatives for potential dental applications using in silico approaches. Methods: The study employed molecular-docking simulations, 100 ns molecular dynamics (MD) simulations, pharmacophore modeling, and in silico toxicity assessments. Key bone-related proteins and receptors were selected to assess the potential of graphene-based materials in dental restorative and regenerative therapies. Results: Molecular-docking simulations revealed strong interactions of Graphene Quantum Dots (GQDs) and sulfur-doped graphene with critical bone-related receptors, suggesting their potential for reinforcing dentin and promoting bone regeneration. MD simulations demonstrated stable complex formations, with occasional fluctuations indicating areas for material optimization. In silico toxicity assessments indicated favorable profiles for high-purity graphene and selected doped graphenes (nitrogen-, fluorine-, and sulfur-doped), while graphene oxide (GO) exhibited concerning toxicity levels, highlighting the importance of mitigating strategies. Conclusions: Graphene and its derivatives exhibit promising biocompatibility and molecular interaction profiles relevant to dental applications. Challenges such as GO’s toxicity and occasional instability in simulations suggest the need for further research into surface modifications and material refinement. These findings pave the way for advancing graphene-based dental materials toward clinical implementation, potentially revolutionizing dental prosthetics and treatments.